The Effectiveness of Listening to Qur'anic Murotal Therapy on Sleep Quality of Patients with Breath Pattern Disorders - Meliana Fitria Salichah; Arina Maliya (STIKes Al-Ma'arif Baturaja, 2024)
Breath pattern disturbances can lead to significant sleep disturbances and negatively impact an individual's physical and mental well-being. One non-pharmacological approach that has emerged as an alternative in addressing sleep disturbances is Murotal Qur'an listening therapy. Murotal therapy is an effective nurse-directed intervention that does not require much cost and is easy to perform. The purpose of this case study is to determine the effectiveness of listening to Qur'anic murotal therapy on the quality of sleep of patients with breathing pattern disorders. The method used is to use a pre-post test design. Researchers took samples with purposive sampling technique as many as 5 respondents who experienced a decrease in sleep quality. The sleep quality instrument uses PSQI (Pittsburg Sleep Quality Sleep) which consists of 7 assessment components that have a score of 0-21. Before the intervention, there were 20% of respondents with very poor sleep quality and 80% of respondents with poor sleep quality. After the intervention, there was a change in 60% of respondents with good sleep quality and 40% of respondents with very good sleep quality. This shows that there is a significant difference before and after the Qur'an murotal therapy. This study concludes that Qur'anic murottal therapy is able to improve sleep quality so that this Qur'anic murottal therapy is effective for patients experiencing sleep disorders.